Pengaruh Inflasi, BI Rate Dan Nilai Kurs Dollar As Terhadap Indeks Harga Saham Gabungan (IHSG) Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Syawitri Wulandari; Sonia Angela Hutabarat; Teresia Sihombing; Michael Simanjuntak; Rafida Khairani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to test either simultaneously or partially. The Effect of Inflation, BI Rate and US Dollar Exchange Value on the Composite Stock Price Index listed on the Indonesia Stock Exchange in the period 2008 - 2018. Using multiple linear regression analysis method to test classical assumptions such as normality, multicollinearity, autocoleration and heteroscedasticity. The results of the F test study showed that the value of Fcount was 9.734> Ftable 4.35 with a significant value of 0.007 <0.005, so that inflation, BI Rate and Exchange Rate together have a significant and significant effect on the Composite Stock Price Index. In the t test, the inflation variable has no and significant effect on the Composite Stock Price Index, the BI Rate has a negative and significant effect on the Composite Stock Price Index and the Exchange Value has a positive and significant effect on the Composite Stock Price Index. With this the coefficient of determination can be seen from the Adjusted R Square value of 0.724. This means that the independent variable can explain the dependent variable by 72.4%, while the remaining 27.6% is explained by other variables not examined. Keywords: BI Rate, IHSG, Inflation, US Dollar Exchange Rate